Athletes, sexual assault, and trials by media : narrative immunity - Waterhouse-Watson, Deb (Routledge research in sport, culture and society, 2013)
Since footballer sexual assault became top news in 2004, six years after the first case was reported, much has been written in the news media about individual cases, footballers and women who have sex with them. Deb Waterhouse-Watson reveals how media representations of recent sexual assault cases involving Australian footballers amount to ""trials by media"", trials that result in acquittal. The stories told about footballers and women in the news media evoke stereotypes such as the ""gold digger"", ""woman scorned"" and the ""predatory woman"", which cast doubt on the alleged victims' cla